A Structural Battery and its Multifunctional Performance. Issue 3 (27th January 2021) - Asp, Leif E.; Bouton, Karl; Carlstedt, David; Duan, Shanghong; Harnden, Ross; Johannisson, Wilhelm; Johansen, Marcus; Johansson, Mats K. G.; Lindbergh, Göran; Liu, Fang; Peuvot, Kevin; Schneider, Lynn M.; et al.
Abstract : Engineering materials that can store electrical energy in structural load paths can revolutionize lightweight design across transport modes. Stiff and strong batteries that use solid‐state electrolytes and resilient electrodes and separators are generally lacking. Herein, a structural battery composite with unprecedented multifunctional performance is demonstrated, featuring an energy density of 24 Wh kg −1 and an elastic modulus of 25 GPa and tensile strength exceeding 300 MPa. The structural battery is made from multifunctional constituents, where reinforcing carbon fibers (CFs) act as electrode and current collector. A structural electrolyte is used for load transfer and ion transport and a glass fiber fabric separates the CF electrode from an aluminum foil‐supported lithium–iron–phosphate positive electrode. Equipped with these materials, lighter electrical cars, aircraft, and consumer goods can be pursued. Abstract : Structural battery composites offer mass‐less energy storage for electrical vehicles and devices. Structural batteries are enabled by the recently discovered multifunctional properties of carbon fibers and the development of a structural electrolyte matrix material. The emergent multifunctional properties reach a level that allows lightweight vehicles and innovations across and beyond all transport modes.